2022
DOI: 10.1186/s12904-022-01056-6
|View full text |Cite
|
Sign up to set email alerts
|

Availability of and factors related to interventional procedures for refractory pain in patients with cancer: a nationwide survey

Abstract: Background Cancer pain may be refractory to standard pharmacological treatment. Interventional procedures are important for quality of analgesia. The aim of the present study was to clarify the availability of four interventional procedures (celiac plexus neurolysis/splanchnic nerve neurolysis, phenol saddle block, epidural analgesia, and intrathecal analgesia), the number of procedures performed by specialists, and their associated factors. In addition, we aimed to establish how familiar home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…Epidural drug infusion therapy is one interventional approach. Most epidural analgesia procedures are performed with a catheter inserted in the lower thoracic or lumbar spine areas and then advanced in the cephalad direction ( 13 ). A previous case report described a patient with metastatic spinal cord compression who received cervical epidural analgesia due to neck pain ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epidural drug infusion therapy is one interventional approach. Most epidural analgesia procedures are performed with a catheter inserted in the lower thoracic or lumbar spine areas and then advanced in the cephalad direction ( 13 ). A previous case report described a patient with metastatic spinal cord compression who received cervical epidural analgesia due to neck pain ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to a nationwide survey in Japan, 47.5% to 79.8% pain specialists had not performed interventional procedures including CPN in the past 3 years, only 18.1% interventional radiology specialists indicated that they conducted CPN by themselves. [56] Several barriers existed for the implementation of the therapies. Studies showed that usually only pain specialists and interventional radiology physicians are able to provide CPN and SND, but a lack of time and training of experts are barriers to the implementation.…”
Section: Management Of Pcrpmentioning
confidence: 99%